Implementasi Siaga Covid 19 Di Kelurahan Sambung Jawa Kota Makassar - Sesilia Rante Pakadang; Sisilia Teresia Rosmaladewi; St Ratnah; Alfrida Monica Salasa; Djuniasti Karim; Dwi Rachmawati Daswi; Arisanty Arisanty; Asmawati Asmawati; Jumain Jumain; Ahmad Murad (Jurnal Pengabdian Kefarmasian, 2022)
Covid 19 (coronavirus disease 2019) is a type of disease caused by the SARS-CoV-2 coronavirus which causes an acute respiratory infection with a very fast and massive spread. The recommended prevention methods are increasing immunity, wearing masks, keeping a distance and washing hands. Products that can be used to prevent COVID-19 are hand sanitizers, disinfectants and imun boosters (food supplements). The purpose of Community Service is to provide counseling on how to prevent Covid 19 and provide training on how to make natural product products for the prevention of Covid 19, namely hand sanitizers, disinfectants and imun boosters (food supplements). Method Service of counseling and training. The implementation of stage 1 has 60 participants (Connect Jawa village team, community representatives, PKK cadres and posyandu). Phase 2 participants 30 people (PKK cadres, posyandu cadres and housewives) The results of community service, the achievement of the counseling target was an increase in knowledge by 28% (hand sanitizer products); 48% (disinfectant product) and 42% (imun booster product). There was a technology transfer process after training on the manufacture of hand sanitizer, disinfectant and imun booster products (food supplements). Outcomes achieved are Natural Disinfectant Pocket Book and Food Supplement Imun Booster Pocket Book Herbal Candy which are published and registered as copyright, publication in Fajar newspaper, community service articles, community service implementation videos. Conclusion. The activity went smoothly, the target achievement was achieved 100%, namely there was an increase in knowledge and technology transfer in the training and the output of 2 books with ISBN, IPR book copyrights and training products.Keywords: training, hand sanitizer, disinfectant, imun booster, Covid 19Covid 19 (coronavirus disease 2019) adalah jenis penyakit yang disebabkan oleh coronavirus jenis SARS-CoV-2 yang menyebabkan infeksi saluran napas akut dengan penyebaran yang sangat cepat dan massif. Cara pencegahan yang dianjurkan adalah meningkatkan imunitas, memakai masker, menjaga jarak dan mencuci tangan. Produk yang dapat digunakan untuk pencegahan Covid 19 berupa hand sanitizer, desinfektan dan imun booster (food suplemen). Tujuan Kegiatan memberikan penyuluhan tentang cara pencegahan Covid 19 dan memberikan pelatihan cara pembuatan produk bahan alam untuk pencegahan Covid 19 yaitu hand sanitizer, desinfektan dan imun booster (food suplemen).  Metode Pengabdian penyuluhan dan pelatihan. Pelaksanaan  tahap 1 peserta 60 orang (tim kelurahan Sambung Jawa, perwakilan masyarakat, kader PKK dan posyandu). Tahap 2 peserta 30 orang (kader PKK, kader posyandu dan ibu rumah tangga) Hasil kegiatan, capaian target penyuluhan terjadi   peningkatan pengetahuan sebesar 28% (produk hand sanitizer); 48% (produk desinfektan) dan 42% (produk imun booster). Terjadi proses alih teknologi setelah pelatihan pembuatan produk hand sanitizer, desinfektan dan imun booster (food suplemen). Luaran yang dicapai adalah Buku Saku Desinfektan Alami dan Buku Saku Food Supplement Imun Booster Permen Herbal yang diterbitkan dan terdaftar sebagai hak cipta, publikasi pada koran Fajar, artikel kegiatan, video pelaksanaan kegiatan. Kesimpulan. Kegiatan berjalan lancar, capaian target tercapai 100% yaitu terjadi peningkatan pengetahuan dan alih teknologi dalam pelatihan dan luaran   2 buku ber ISBN, HKI hak cipta buku dan produk pelatihan.Kata Kunci:  pelatihan, hand sanitizer, desinfektan, imun booster, Covid 19